A New Frontier: The Convergence of Nanotechnology, Brain Machine Interfaces, and Artificial Intelligence - Silva, Gabriel A. (Frontiers in Neuroscience, 2018)
A confluence of technological capabilities is creating an opportunity for machine learning and artificial intelligence (AI) to enable 'smart' nanoengineered brain machine interfaces (BMI). This new generation of technologies will be able to communicate with the brain in ways that support contextual learning and adaptation to changing functional requirements. This applies to both invasive technologies aimed at restoring neurological function, as in the case of neural prosthesis, as well as non-invasive technologies enabled by signals such as electroencephalograph (EEG). Advances in computation, hardware, and algorithms that learn and adapt in a contextually dependent way will be able to leverage the capabilities that nanoengineering offers the design and functionality of BMI. We explore the enabling capabilities that these devices may exhibit, why they matter, and the state of the technologies necessary to build them. We also discuss a number of open technical challenges and problems that will need to be solved in order to achieve this.